Effect of male circumcision on the prevalence of high-risk human papillomavirus in young men: results of a randomized controlled trial conducted in Orange Farm, South Africa - Auvert, Bertran (University of Chicago Press, 2009)
INTRODUCTION: A causal association links high-risk human papillomavirus (HR-HPV) and cervical cancer, which is a major public health problem. The objective of this study was to investigate the association between male circumcision (MC) and HR-HPV prevalence among young men. METHODS: We used data from a male circumcision trial conducted in Orange Farm (South Africa) among men aged 18 to 24. Urethral swabs were collected during a period of 262 consecutive days among participants from the intervention (circumcised) and control (uncircumcised) groups who were reporting for a scheduled follow-up visit. Swabs were analyzed using PCR. HR-HPV prevalence rate ratios (PRRs) were assessed using univariate and multivariate log-Poisson regression. RESULTS: In an intention-to-treat analysis, HR-HPV prevalences among intervention and control groups were 14.8% (94/637) and 22.3% (140/627), respectively, with a PRR of 0.66 (0.51–0.86) P=0.002. Controlling for propensity score and confounders (ethnic group, age, education, sexual behavior including condom use, marital status, and HIV status) had no effect on the results. CONCLUSIONS: This is the first randomized controlled trial that shows a reduction in urethral HR-HPV infection following male circumcision. This finding explains why women with circumcised partners are less at risk of cervical cancer than other women.